Hubungan Antara Tingkat Pengetahuan Dismenorea Dan Penanganan Dismenorea Pada Siswi Kelas 8 SMP Negeri 7 Wonogiri - Fadmawati, Andri, dr. Sri Wahyu Basuki, M.Kes, dr. Dodik Nursanto (2015)
Background: Dysmenorrhea was menstrual pain, these conditions can be treated medically and non-medically. In the research that has been done, there was 78, 3% students had less Dysmenorrhea understanding. The lack of student's ability was caused by getting less of information sources. The bad treatment of Dysmenorrhea can be seen from the lowest respondent who doing the Dysmenorrhea treatment (7,5%). Dysmenorrhea is detected could reduce the concentration and academic achievement moreover until disturb the social activities. The correlation test that had been used was Pearson correlation test. Method: The kind of the research was observational analysis through cross sectional approach. The samples are 37 of grade students who had been felt menarche. The collection of samples was doing by simple randomly which the technique of collecting data by collecting all of respondents then taken the respondent who had even number. The collecting the data is by given questionnaire of the action treatment and Dysmenorrhea understanding. Results: Based on the result of the research, the average score of understanding is 751,35 and the average score of treatment is 59,64. The correlation test that had been used was Pearson correlation test. But, after had been doing the normality test which Saphiro-Wilk, it found the data not in normal distributed so it had been doing Spearman altefnative correlation test. The result of analysis the relationship between understanding and treatment of Dysmenorrhea namely (r: -0,131 and p: 0,439). Conclusion: There is no correlation between the level of Dysmenorrhea understanding and Dysmenorrhea treatment toward grade students of SMP N 7 Wonogiri.